Viver na moradia é...: a dialética entre o sofrimento ético-político e a luta por reconhecimento dos estudantes na moradia estudantil UFSCar - Ferreira, João Felipe Dias (Universidade Federal de São Carlos, 2025)
Mental health care is permeated by a political dimension, whose current paradigm is the psychosocial care model. Furthermore, the health-disease process must be understood in a way that is linked to the social context in which it is embedded, so that social determinants of health produce inequities of suffering in a society also determined by the neoliberal economic context of psychic management. In this context, youth develops amidst various risks of suffering, which manifests itself in specific ways in the university context. This scenario is aggravated by insecurities related to student assistance, making it necessary to investigate experiences in particular contexts of vulnerable populations, such as Student Housing. Given this, the present study aimed to investigate the dimensions and repercussions of psychic suffering among students at the UFSCar-São Carlos Student Housing. A participatory investigation was carried out, in which 25 students residing in the Residence Hall participated in a first stage of quality of life mapping, using the WHOQOL-bref instrument. In a second stage, 11 participants were distributed into 2 operational focus groups in order to identify the psychosocial determinants of suffering and impacts on life trajectories, as well as to provide support and address these issues. A generally low-to-medium quality of life was found in the Student Housing, varying according to different social and material markers. Furthermore, the Thematic Analysis of the qualitative data resulted in a complex picture of "challenges" and "confrontations" dialectically articulated in the students' life experience. This dialectic was interpreted as the coexistence of ethical-political suffering and the possibility of fighting for recognition to mitigate it. It is concluded that the articulated strengthening of institutional measures for permanence and collective strategies for resistance are necessary and possible to address mental illness in Student Housing.
Living in student housing is…: the dialectic between ethical-political suffering and the struggle for recognition of students in UFSCar student housing
Keywords: Saúde mental; Moradia estudantil; Psicologia social; Sofrimento ético-político; Luta por reconhecimento; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO; 4. Educação de Qualidade